2012
DOI: 10.1364/oe.20.015086
|View full text |Cite
|
Sign up to set email alerts
|

Focusing through dynamic scattering media

Abstract: We demonstrate steady-state focusing of coherent light through dynamic scattering media. The phase of an incident beam is controlled both spatially and temporally using a reflective, 1020-segment MEMS spatial light modulator, using a coordinate descent optimization technique. We achieve focal intensity enhancement of between 5 and 400 for dynamic media with speckle decorrelation time constants ranging from 0.4 seconds to 20 seconds. We show that this optimization approach combined with a fast spatial light mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 28 publications
0
68
1
Order By: Relevance
“…We may also define a different optimization parameter that depends on both the coupling efficiency and the correlation with the desired mode patterns. Given the fact that the algorithm described here has been widely used for optical focusing through diffusive media [19][20][21][22][23][24][25][26][27], where optical power is a critical factor, the issue of coupling efficiency should not become a major hurdle for our AO-based approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We may also define a different optimization parameter that depends on both the coupling efficiency and the correlation with the desired mode patterns. Given the fact that the algorithm described here has been widely used for optical focusing through diffusive media [19][20][21][22][23][24][25][26][27], where optical power is a critical factor, the issue of coupling efficiency should not become a major hurdle for our AO-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall framework of the AObased approach should still apply. Again, this expectation is based on the successful demonstration of AO-based focusing [19][20][21][22][23][24][25][26][27], which involves hundreds, if not tens of thousands independent scattering channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Popoff et al demonstrated that the WFS approach can be parallelized to measure a significant fraction of the medium's transmission matrix [18,19]. In view of biomedical applications, several research groups have developed techniques for highspeed focusing and transmission matrix measurements through turbid media [20][21][22][23]. Van Putten et al employed WFS to create a scattering lens for high-resolution imaging [24,25].…”
Section: Spatial Control Of Scattered Lightmentioning
confidence: 99%